Prognostic significance of bone invasion for oral cavity squamous cell carcinoma considered T1/T2 by American joint committee on cancer size criteria. Issue 6 (30th July 2013) - Fried, David; Mullins, Brandon; Weissler, Mark; Shores, Carol; Zanation, Adam; Hackman, Trevor; Shockley, William; Hayes, Neil; Chera, Bhishamjit S.
ABSTRACT Background It is unclear whether bone invasion in small oral cavity squamous cell carcinomas (OCSCC) results in worse prognosis. Methods Two hundred fifty‐four patients with OCSCC were identified and divided into 3 cohorts: (1) ≤4 cm with no bone invasion; (2) ≤4 cm with bone invasion; and (3) ≥4 cm or other factors (eg, skin invasion, deep muscle invasion) that would qualify for American Joint Committee on Cancer (AJCC) T4 classification aside from bone invasion. Depth of bone invasion (none, cortical, or medullary) was also recorded. Results Cohorts 1 and 2 had similar outcomes. Cohort 3 had lower rates of regional control (p = .04), disease‐specific survival (DSS; p < .01), and overall survival (OS; p < .01). On multivariate analysis, margin status and medullary bone invasion were associated with worse outcomes. Conclusion Bone invasion does not seem to significantly influence outcomes in patients with small primary tumors treated with surgery/radiation. Medullary bone invasion seems to result in reduced rates of control and survival. © 2013 Wiley Periodicals, Inc. Head Neck 36: 776–781, 2014